Navigating the uncertainty of precision cancer screening: The role of shared decision-making - Joseph H. Gallagher; Jason L. Vassy; Marla L. Clayman (Elsevier, 2023)
Objective: Describe how applying a shared decision making (SDM) lens to the implementation of new technologies can improve patient-centeredness. Methods: This paper argues that the emergence of polygenic risk scores (PRS) for cancer screening presents an illustrative opportunity to include SDM when novel technologies enter clinical care. Results: PRS are novel tools that indicate an individual's genetic risk of a given disease relative to the population. PRS are anticipated to help identify individuals most and least likely to benefit from screening. However, PRS have several types of uncertainty, including validity across populations, disparate computational methods, and inclusion of different genomic data across laboratories. Conclusion: Implementing SDM alongside new technologies could prove useful for their ethical and patient-centered utilization. SDM's importance as an approach to decision-making will not diminish, as evidence, uncertainty, and patient values will remain intrinsic to the art and science of clinical care. Innovation: SDM can help providers and patients navigate the considerable uncertainty inherent in implementing new technologies, enabling decision-making based on existing evidence and patient values.